Online Real Estate Feed Reader - Ibrahim, Ahmad Ridzuan (Universiti Teknologi PETRONAS, 2009)
This report basically discusses the preliminary research done and basic understanding of the proposed topic, which is "Online Real Estate Feed Reader". This online real estate feed reader is an idea in order to give services to people who lives in the developed area where people will face the difficulty to find land or houses. This also gives people an easy alternative way to find the agent for real estate from using the traditional way like newspaper or directly to agent. User can just click search button to display the result and also can just subscribe RSS in order to get time to time updated. This Online Real Estate feed reader website with the objective to help the user to search exactly the real estate website available from internet and not with the anonymous result which sometimes no related at all to the real estate web. User also can get information about what they are searching in term of description, contact person or picture from this online real estate feed reader, this will make sure user will get right information from the selected real estate website. The website also contains with the RSS feeds where it can be subscribe from the top of the page, this RSS will be update frequently automatically will show the outline of the information and also the picture if there are available. For the introduction, the scope for this online real estate feed reader will be focusing to search or the of real estate in KL area only, where this website only lists the real estate from KL area and stores all the information into the database. The methodology use in this project is prototyping methodology, where it consist of several phase which are planning, analysis, design and implementation phase, which the planning, analysis and design are perform repeatedly until the system is completed .The analysis also has been perform under result and discussion session, most of the user give a positive feedback for the system and for the conclusion author hope this project will be success and achieve it scope and objectives like planned and user can get benefit by using this system.